The Effect of Brand Image, Promotion, and Product Design on Purchasing Decisions of Morinaga Chil School Milk - Annisa Sanny; Muhamad Toyib Daulay (Proceeding of The International Conference on Economics and Business, 2023)
This research was to determine the effect of Brand Image, Promotion, and Product Design on Purchase Decisions for Morinaga Chil School Milk at Brastagi Supermarket. The analysis used is associative analysis, this research method is quantitative. The sample in this research is 100 respondents. The results obtained from this study indicate that their image partially and significantly influences purchasing decisions, and promotions partially and significantly influence purchasing decisions. Product Design partially has no effect and is not significant in Purchasing Decisions. Brand Image, Promotion, and Product Design simultaneously and significantly affect Purchase Decisions. the acquisition value of Adjusted R square 0.865 can be called the coefficient of determination, this means 0.865 (86.5%) Consumer Purchase Decisions can be obtained and explained by brand image, promotion, and product design